2005
DOI: 10.1038/sj.npp.1300870
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Hypothalamic Neurotensin System

Abstract: This study used B Â D recombinant inbred mice to detect and localize genes that control the hypothalamic neurotensin (NT) system. Abundance of transcripts that encode NT and NT receptors 1, 2, and 3 (NTR1, NTR2, and NTR3) in total hypothalamic RNA was the quantitative trait measured. Analysis of transcript abundance data revealed associations with quantitative trait loci (QTL) for NT transcript abundance (NTta) on chromosome 1, 3, 6, 7, 8, and 9; for NTR1ta on chromosome 3, 8, 12, and X; for NTR2ta on chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…For CART, the B6 parent strain had a lower C t (i.e., higher transcript abundance) than the D2 strain. We have observed similar SDP amongst B6 and D2 strains in previous studies of hypothalamic peptide transcripts in our laboratory (Garlow et al, 2005(Garlow et al, , 2006. Comparison of the SDP for hypothalamic CART and corticotrophin-releasing factor (Garlow et al, 2005) transcription abundance expression reveals a significant correlation in strain mean transcript abundance between the targets (Pearson's r=0.46, p<0.0192).…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…For CART, the B6 parent strain had a lower C t (i.e., higher transcript abundance) than the D2 strain. We have observed similar SDP amongst B6 and D2 strains in previous studies of hypothalamic peptide transcripts in our laboratory (Garlow et al, 2005(Garlow et al, , 2006. Comparison of the SDP for hypothalamic CART and corticotrophin-releasing factor (Garlow et al, 2005) transcription abundance expression reveals a significant correlation in strain mean transcript abundance between the targets (Pearson's r=0.46, p<0.0192).…”
Section: Resultssupporting
confidence: 54%
“…See Garlow et al, (2005Garlow et al, ( 2006 for complete RNA quantification methods. Amplification and detection primers for RT-PCR assays were from ABI "Assays-On-Demand" and included CART (ABI assay # Mm00489086; Accession # NM_013732.3), which generated an amplicon of 71 base pairs.…”
Section: Rna Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…This confirmed that genes located on chromosome 1, which affect nerve system development (16), and on chromosome 19, which usually associate with genetic diseases (17), were mainly correlated with the development of NF1. The key cluster of genes that stimulate nerve growth on chromosomes 1 and 19 require identification in future studies.…”
supporting
confidence: 68%